Structure model of bistable current switching in CdS films - Panchekha, P.A.; Novikov, V.A. (Functional Materials, 2004)
The VCC of CdS films in static and dynamic modes have been measured. A number of new kinetic features has been revealed for the electrically stimulated switching between two stable states. The states differ in their electric conduction levels by a factor of 10⁴ and are kept after the external power supply is switched off. A new structure model of the bistable switching has been proposed. Измерены BAX пленок CdS в статическом и динамическом режимах. Обнаружен ряд новых особенностей кинетики электростимулированного переключения между двумя устойчивыми состояниями, которые отличаются по уровню электропроводности в 10⁴ раз и сохраняются после отключения внешнего напряжения. Предложена новая структурная модель бистабильного переключения. Отримано BAX плівок CdS у статичному та динямічному режимах. Виявлено ряд нових особливостей кінетики електростимульованого перемикання між двома стабільними станами, які відрізняються за рівнем електропровідності в 10⁴ разів і зберігаються після відключення зовнішньої напруги. Запропоновано нову структурну модель бістабільного перемикання.